2009
DOI: 10.1007/s10495-009-0338-6
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and apoptosis: neural crest cells and neural tube

Abstract: Birth defects resulting from diabetic pregnancy are associated with apoptosis of a critical mass of progenitor cells early during the formation of the affected organ(s). Insufficient expression of genes that regulate viability of the progenitor cells is responsible for the apoptosis. In particular, maternal diabetes inhibits expression of a gene, Pax3, that encodes a transcription factor which is expressed in neural crest and neuroepithelial cells. As a result of insufficient Pax3, cardiac neural crest and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 183 publications
1
40
0
Order By: Relevance
“…Although the underlying mechanism is not very clear, we and others have shown that NTDs are closely related to increased apoptosis in the neural epithelium [4,11,21,33]. It has been known that PKCδ is critical in cell apoptosis [3436], and deletion of pkc δ significantly reduced the apoptosis in different tissues and models.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Although the underlying mechanism is not very clear, we and others have shown that NTDs are closely related to increased apoptosis in the neural epithelium [4,11,21,33]. It has been known that PKCδ is critical in cell apoptosis [3436], and deletion of pkc δ significantly reduced the apoptosis in different tissues and models.…”
Section: Discussionmentioning
confidence: 88%
“…Maternal hyperglycemia disturbs intracellular signaling leading to increases in stress conditions which, in turn, trigger programmed cell death (apoptosis) in the neural tube of the embryo [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Diabetic patients reveal distorted glucose fat along with protein metabolism. This dysfunction considerably changes the cellular microenvironment in various different tissue types, leading to "diabetic complications" including microvascular complications such as diabetic nephropathy, neuropathy and retinopathy, along with macrovascular complications including accelerated atherosclerosis causing ischaemic heart and cerebrovascular disease [28]. Diabetes affects both glucose and lipid metabolism.…”
Section: Dissuasionmentioning
confidence: 99%
“…Diabetes affects both glucose and lipid metabolism. [29] In the post prandial state elevated serum insulin increases lipoprotein lipase activity in adipose tissue and promotes fuel storage as triglycerides in normal metabolism [28]. The deficiency of insulin reduces the activity level of lipoprotein lipase, therefore leading to unbalanced lipoprotein metabolism during diabetes [30].…”
Section: Dissuasionmentioning
confidence: 99%
“…Interestingly, anencephaly and spina bifida occur more commonly in infants born to women with diabetes [5, 6]. Here we present a unique case of a stillborn fetus delivered by a Type I diabetic mother with both eosinophilic pancreatitis and anencephaly.…”
Section: Introductionmentioning
confidence: 99%